The Rate Performance of Two-Dimensional Material-Based Battery Electrodes May Not Be as Good as Commonly Believed - Coleman, Jonathan (My University, 2020)
Two-dimensional (2D) materials show great potential for use in battery electrodes and are believed to be particularly promising for high-rate applications. However, there does not seem to be much hard evidence for the superior rate performance of 2D materials compared to non-2D materials. To examine this point, we have analyzed published rate-performance data for a wide range of 2D materials as well as non-2D materials for comparison. For each capacity-rate curve, we extract parameters that quantify performance which can then be analyzed using a simple mechanistic model. Contrary to expectations, by comparing a previously proposed figure of merit, we find 2D-based electrodes to be on average ∼40 times poorer in terms of rate performance than non-2D materials. This is not due to differences in solid-state diffusion times which were similarly distributed for 2D and non-2D materials. In fact, we found the main difference between 2D and non-2D materials is that ion mobility within the electrolyte-filled pores of the electrodes is significantly lower for 2D materials, a situation which we attribute to their high aspect ratios.
Keywords: Anode rate; Cathode; Current; Diffusion coefficient; Diffusivity; Model; Nanosheet